INTEGRATING ICT IN ISLAMIC RELIGIOUS EDUCATION: ENHANCING LEARNING OUTCOMES AND OVERCOMING CHALLENGES IN THE 21ST CENTURY - Muflikhatun; Pahrudin, Agus; Jatmiko, Agus; Koderi; Azad, Inamul (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2025)
This study explores the integration of Information and Communication Technology (ICT) in Islamic Religious Education (PAI), aiming to enhance learning outcomes and address challenges in adapting to modern educational demands. Using a literature review methodology, this research synthesizes studies published between 2015 and 2023, focusing on the effectiveness of ICT tools, the types of digital resources used in PAI, and the barriers faced by educators in implementing these technologies. The findings indicate that ICT significantly improves student engagement, motivation, and comprehension in PAI subjects, particularly through multimedia tools, mobile applications, and e-learning platforms. However, challenges such as inadequate infrastructure, digital literacy among teachers, and the digital divide between urban and rural areas limit the widespread use of ICT in PAI classrooms. The study highlights the need for increased investments in infrastructure and continuous professional development for teachers to bridge these gaps. Additionally, it calls for policy support at both institutional and governmental levels to facilitate the integration of ICT in religious education. The novelty of this research lies in its focus on the specific application of ICT in PAI, offering insights into how digital tools can modernize Islamic education while preserving its core values. The findings provide valuable recommendations for educators and policymakers to enhance ICT integration in PAI and ensure its effective use in the 21st century.